Penerapan Relaksasi Pernapasan Diafragma untuk Meningkatkan Relaksasi Otot Napas pada Pasien dengan Asma di Ruang Rawat Inap - Prisca Ika Pratiwi; Novita Elisabeth Daeli; Srimiyati Srimiyati (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
Asthma is a chronic inflammatory disease of the airways characterized by reversible bronchoconstriction, mucus hypersecretion, and bronchial hyperresponsiveness. This condition causes shortness of breath, coughing, wheezing, and increased respiratory rate which impacts increased respiratory muscle work. One of the non-pharmacological interventions that can be applied in nursing practice is diaphragmatic breathing relaxation to help improve breathing patterns and increase respiratory muscle relaxation. Objective: To analyze the application of diaphragmatic breathing relaxation in improving respiratory muscle relaxation in asthma patients in the inpatient ward. Method: The study used a case study design with an Evidence Based Practice (EBP) approach. The research subjects were three asthma patients who experienced increased respiratory frequency. The intervention was carried out for three days in the form of structured diaphragmatic breathing exercises. Data were collected through nursing assessment, observation of respiratory frequency before and after the intervention, and evaluation of patient responses. Results: Before the intervention, all respondents experienced tachypnea with the use of accessory respiratory muscles. After three days of diaphragmatic breathing relaxation, the respiratory rates of all three respondents returned to normal (12–20 breaths/minute), respiratory muscle tension decreased, and the patients appeared more relaxed. Conclusion: Diaphragmatic breathing relaxation is effective in increasing respiratory muscle relaxation and stabilizing respiratory rate in asthmatic patients. This intervention can be used as part of non-pharmacological nursing care for patients with respiratory system disorders.